Using Semantic Web, Ontologies and Blogs for Knowledge Identification, Organisation and Reuse. - Mohd. Kassim, Azleena; Cheah, Yu-N (2007)
In this paper, we propose an approach to make knowledge-based blogging more interesting, reliable and sophisticated by using semantic web with ontology in the blogging environment. The aim of our research is to realise the knowledge management processes of identification, organisation and reuse (adaptation and application) via the blogging environment for them to be available to users in a seamless application. To achieve knowledge identification, we employ natural language processing techniques coupled with ontologies to identify possible categories of new blog posts. For knowledge organisation, we finalise the categorisation of blog posts and store them into a repository. Finally, in knowledge reuse, we create semantic links between blog posts and other related documents. These processes are integrated in a blogging framework which we call SEMblog.